Sistem Keamanan Sepeda Motor - Padang, Junelka Lisendra; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The increase in theft motorcycle is influenced by the increased of purchasing power towards motorbikes. The theft was due to lack of security in those motorcycles. Form this problem, a motorcycle safety system is made. To make this system an Arduino Uno with C language programming is required to turn on and turn off a motorcycle. Form the test results, the system can turn on and turn off motorcycle when it is needed form different place to avoid that theft. If the motorcycle ON, the LED indicator lamp will turn on and if the motorcycle is OFF the LED indicator light will turn off too. Keywords : Security System, Motorcycle, Arduino Uno, Language C, LED Indicator Light.